2021
DOI: 10.1007/s43678-020-00062-y
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in emergency medical services utilization during early stages of the COVID-19 pandemic in British Columbia

Abstract: Objective To date in the COVID-19 pandemic, there has been a decrease in patients accessing emergency health services, (EHS) but research has been conducted in areas with a very high incidence of COVID-19. In an area with a low COVID-19 incidence, we estimate changes in EHS use. Methods We compared EHS encounters in British Columbia from March 15 (the date of school and business closures) to May 15, 2020, when compared to the same period in 2019. We categorized EHS encounters into 18 presenting complaints and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
0
20
1
Order By: Relevance
“…Unlike previous investigators, 3,16 we observed an increased demand for EMS and decreased emergency department and urgent care centre volumes. 17 Despite shifts in the acuity of emergency department and urgent care centre patients, a greater proportion of high-priority EMS dispatches was not observed, which suggests that the EMS system was seeing a different composition of patients than emergency departments and urgent care centres.…”
Section: Discussioncontrasting
confidence: 96%
“…Unlike previous investigators, 3,16 we observed an increased demand for EMS and decreased emergency department and urgent care centre volumes. 17 Despite shifts in the acuity of emergency department and urgent care centre patients, a greater proportion of high-priority EMS dispatches was not observed, which suggests that the EMS system was seeing a different composition of patients than emergency departments and urgent care centres.…”
Section: Discussioncontrasting
confidence: 96%
“…6,49 In addition, independent of the reluctance to seek help, patients with severe acute illness may have deteriorated due to reduced access to emergency health services, such as emergency department overcrowding and delayed ambulance response time. 17,19,50 The relative importance of each causal pathway is likely to differ between cities, as our study found that OHCA of asphyxial etiology was increased in some, but not all studies.…”
Section: Discussionmentioning
confidence: 70%
“…These may include the interruption of primary care for chronic diseases, reduced willingness to seek early treatment for acute symptoms leading to increased risk of OHCA, as well as worsened prognosis due to less e cient bystander, ambulance, and hospital interventions for OHCA. [11][12][13][14][15] These treatment processes may have, in turn, been adversely affected by reduced bystander willingness to render life-saving interventions, 16,17 altered airway management protocols, 18 or even overwhelmed healthcare facilities. 19 Accordingly, the aim of this study was to evaluate the impact of the COVID-19 pandemic on the incidence, characteristics, and clinical outcomes of OHCA through a systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, the disruption (or deprioritization) of “non-essential” health services provision during the pandemic may have adversely affected the ongoing management of chronic disease, leading to increased individual-level risk [ 6 , 51 ]. In addition, independent of the reluctance to seek help, patients with severe acute illness may have deteriorated due to reduced access to emergency health services, such as emergency department overcrowding and delayed ambulance response time [ 17 , 19 , 52 ]. The relative importance of each causal pathway is likely to differ between cities, as our study found that OHCA of asphyxial etiology was increased in some, but not all studies.…”
Section: Discussionmentioning
confidence: 99%
“…These may include the interruption of primary care for chronic diseases, reduced willingness to seek early treatment for acute symptoms leading to increased risk of OHCA, as well as worsened prognosis due to less efficient bystander, ambulance, and hospital interventions for OHCA [ 11 15 ]. These treatment processes may have, in turn, been adversely affected by reduced bystander willingness to render life-saving interventions [ 16 , 17 ], altered airway management protocols [ 18 ], or even overwhelmed healthcare facilities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%